Medieval art and architecture at Ely Cathedral.
1 online resource
Keywords: This is the second volume in the series launched by the British Archaeological Association in which are to be published the transactions of the annual conferences devoted to the study of a major medieval monument and its surrounding area. As in the case of the first volume the unavoidable delay in publishing the transactions has meant that some of the papers are not in the form that they were delivered to the conference and that not all the papers were available for publication in the present volume. The editors have therefore taken the opportunity to include some additional plates, especially plans, which may not be referred to directly in any of the papers but which, it is felt, will make the volume a more useful contribution to the study of this remarkable building. This Volume includesL Sutton in the Isle of Ely and its Architectural Context (Richard Fawcett); Medieval Timberwork at Ely (John Fletcher); The Fourteenth-Century Tile Pavements in Prior Crauden's Chapel and in the South Transept (Lawrence Keen); Ely Cathedral: the Fourteenth-Century Work (Nicola Coldstream).